Magnetic properties of acicular ultrafine iron particles - Varanda, L. C.; Goya, G. F.; Morales, M. P.; Marques, RFC; Godoi, RHM; Jafelicci, M.; Serna, C. J. (Institute of Electrical and Electronics Engineers (IEEE), 2002)
Magnetic properties of acicular (similar to60 and similar to200 nm) iron particles, obtained by reduction of alumina-coated goethite particles, are reported. X-ray diffraction and Mossbauer spectroscopy showed that the particles consist of a alpha-Fe core and a thin surface layer of maghemite. Magnetization data indicated an improvement of similar to28% in the saturation magnetization, coercive field, and squareness for particles with similar to60 nm. This magnetic property enhancement of the present particles, whose size is 40% smaller than those commercially available, could result in a similar decrease of the bit-size for higher density of magnetic media.
Keywords: coercivity; magnetic recording; magnetic variable measurements; metal ultrafine particles; passivation